2019
DOI: 10.3390/children6030039
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Systems to Support Inclusive Education for Children Requiring Medical Care, Current Status of Such Support, and Related Challenges—Based on the Results of Surveys Involving Departments of Education Supporting their Enrollment in General Schools

Abstract: Based on the results of our surveys involving several municipal departments of education that support the enrollment of children requiring medical care in general schools, this report describes Japanese systems to support inclusive education for these children, the current status of such support, and related challenges. The municipal departments of education that systematically support inclusive education for children requiring medical care began to promote such education in their communities before the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The results also showed that the national and county governments were not deemed to be doing much for SNE in Machakos Sub County. These results are contrary to the findings by Yamamoto and Moriwaki (2019) in Japan, who found that municipal governments were instrumental in offering medical support for SNE learners. The difference in government support can be attributed to the existing legal frameworks, which allocate resources to different government agencies, which is contrary to Dalton et al (2012), who found clear policies in place in South Africa.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results also showed that the national and county governments were not deemed to be doing much for SNE in Machakos Sub County. These results are contrary to the findings by Yamamoto and Moriwaki (2019) in Japan, who found that municipal governments were instrumental in offering medical support for SNE learners. The difference in government support can be attributed to the existing legal frameworks, which allocate resources to different government agencies, which is contrary to Dalton et al (2012), who found clear policies in place in South Africa.…”
Section: Resultscontrasting
confidence: 99%
“…In a study based in Japan, Yamamoto and Moriwaki (2019) studied the systems in place to support special education for children with disabilities. The study's target population was municipal employees in the education departments in Yokohama City and Toyonaka City.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The special education regulations in Japan advocate for the "social model" where the problem is within the society or the environment, but this court case decision is not based on a social model, but rather the "medical model" where the problem is within the individual. Yamamoto and Moriwaki (2019) surveyed the mechanisms of Yokohama City, Kanagawa Prefecture, and Toyonaka City, Osaka Prefecture, which have been engaged in the education of children with medical care needs from early on. The result revealed that the background of the initiative was the introduction of a school support system based on the viewpoint of human rights education, not just disabilities.…”
Section: Implications On School Placementmentioning
confidence: 99%
“…Services and needs of these children vary by their conditions, but they may have ventilators and gastrostomy tube (G-tube) and require tracheostomy care and tube feeding. Some CMCN also use specialized equipment such as customized wheelchairs and stretchers (Yamamoto & Moriwaki, 2019).…”
Section: Introductionmentioning
confidence: 99%